An experimental study on low-velocity impact behavior of carbon fiber/pineapple leaf fiber hybrid laminates for automotive applications - Xiao, Hanyue; Sultan, Mohamed Thariq Hameed; Shahar, Farah Syazwani; Nayak, Suhas Yeshwant (Taylor and Francis, 2025)
This work characterizes the low-velocity impact (LVI) failure behaviors of three bio/synthetic hybrid laminates based on carbon fiber (C) and pineapple leaf fiber (P). The effect of aluminum (A) addition and its position were investigated by flexural tests, peak force, force–displacement curves, energy–time curves, visual inspection, and infrared thermography (IR). The flexural tests reveal that fiber-reinforced polymer (FRP) CPC composites exhibit superior flexural properties than fiber metal laminates (FMLs). FMLs with aluminum as skin sheets (ACPCA) show a 62.2% improvement in flexural strength (312.02 MPa) over those with internal aluminum (CAPAC). LVI results show that FMLs outperform FRP in impact performance, with ACPCA and CAPAC achieving peak force improvements of 266.22% (2.71 kN) and 209.50% (2.29 kN) over CPC (0.74 kN), respectively. The results emphasize the significance of A position, where ACPCA exhibits full rebound behavior while CAPAC shows partially rebound at 15J impact energy. Visual inspection and IR results corroborate LVI findings, indicating increased delamination at higher energies. Notably, IR provides critical insights into damage progression and internal structural changes, highlighting areas of delamination and deformation around V-type damage. These results suggest that the ACPAC provides a balance between bending and impact resistance, assisting material selection in automotive applications.